Devolatilization studies of oil palm plantation residues via torrefaction process - Yu Xun, Teo (2015)
Biomass represents a type of renewable energy source that will play a substantial role in the future global energy balance in terms of energy security and carbon-neutral fuel. However, raw lignocellulosic biomass presents several undesired properties such as low energy density, hygroscopic nature, and low bulk density that do not permit its direct exploitation. Torrefaction, an emerging thermal pretreatment process, is acknowledged to improve the fuel properties of raw biomass towards an efficient renewable energy supply. This paper investigates the fuel characteristics of OPF and OPT at temperatures: 200˚C, 250˚C, and 300˚C at a constant heating rate of 10˚C/min and 30 min residence time. The torrefied products were characterized in terms of their moisture content, calorific value, mass an energy yield. Prediction of calorific value based on the colour of torrefied biomass was also presented here. Bomb calorimeter was used to measure the calorific value in order to calculate mass and energy yield for analysis. In addition, Fourier Transform Infrared (FTIR) Spectroscopy, Thermogravimetric Analysis (TGA), and Derivative Thermogravimetric (DTG) analysis were performed to investigate the changes of lignocellulosic physicochemical properties of the studied materials. As a result, both OPF and OPT with calorific value of 16.41 MJ/kg and 17.41 MJ/kg were improved to 22.46 MJ/kg and 25.48 MJ/kg respectively after torrefaction at 300˚C. The mass yield for both samples decrease at elevated torrefaction temperature while retaining their energy yield between 90-100%. The degradation behaviours of lignocellulosic components: hemicellulose, cellulose, and lignin were discussed through FTIR, TGA, and DTG analysis. Meanwhile, the improved hydrophobic characteristic was also justified. This work concludes that OPF and OPT made a good biomass for torrefaction purpose which can be upgraded to universal energy commodity.